A Study on Trust in God in Juvenile Delinquents - Mualla Yıldız; Fatma Kenevir (Ankara Üniversitesi İlahiyat Fakültesi Dergisi)
Adolescence is a critical stage of life in the triangle of education, family, and peers for young people. During adolescence, young people might need to overcome many hassles and fluctuations. This study aimed to investigate the relationship between the levels of trust in God and some variables such as education levels, mother’s literacy, family unity, drug addiction, having a close friend at the correctional facility, repetitive crime, and experience of running away from home in male juvenile delinquents. This study is an associational research and the population of the study was 500 male adolescents who were in the Ankara Sincan Youth Closed Prison and Correctional Center, Turkey. 389 male adolescents were selected from the research population through purposeful sampling as the sample. In this study, the attitudes of the sample were measured by the Scale of the Image of God. The questions were asked in a closed-ended way, and the data was analyzed by using the SPSS software (version 22). T-Test and ANOVA were utilized to compare the means. The data revealed that the levels of the trust in God of the adolescents differed depending on using addictive substances, repetitive crime, criminal peers, and education level. The male adolescents whose close friends were in prison, those who used drugs, those who were involved in repetitive crimes, and those who had a low education level had a lower level of trust in God than others. It has been deduced that the social environment of adolescents can be consequential in the development of religious perceptions, and that negative life experiences, as well as adverse social conditions, inhibit the development of trust in God.